Physical characterization of SCP1, a giant linear plasmid from Streptomyces coelicolor. - Kinashi, H (1991)
SCP1, coding for the methylenomycin biosynthesis genes in Streptomyces coelicolor, was shown to be a giant linear plasmid of 350 kb with a copy number of about four by analysis with pulsed-field gel electrophoresis. A detailed physical map of SCP1 was constructed by extensive digestion with six restriction endonucleases, by DNA hybridization experiments, and finally by cloning experiments. SCP1 has unusually long terminal inverted repeats of 80 kb on both ends and an insertion sequence at the end of the right terminal inverted repeat. Analysis by pulsed-field gel electrophoresis in agarose containing sodium dodecyl sulfate revealed that a protein is bound to the terminal 4.1-kb SpeI fragments derived from both ends of SCP1. Treatment with lambda exonuclease or exonuclease III and SpeI digestion also indicated that the 5' ends of SCP1 are attached to a protein.